PENGARUH SEXUAL SATISFACTION TERHADAP TINGKAT KESEHATAN MENTAL IBU RUMAH TANGGA DI SUMBAWA - Hasri Rosadi, Fitra; Hartono, Roni (Jurnal TAMBORA, 2021)
Sexual satisfaction is a feeling of satisfaction obtained from sexual activitybetween husband and wife. In some cases it was found that wives tended not toget sexual satisfaction. This can have a negative impact onwife or both parties because sexual satisfaction is an indicatorthe joy of marriage and a source of individual psychic energy. Hence, this studyaims to determine the effect of sexual satisfaction on health levelshousewife mentality.This research uses a quantitative approach with the type of causal researchcomparative. Data were collected using a scale, namely the scale of sexual satisfaction(NSSS) and mental health scale (WEMWBS). The number of research subjectsare 89 out of 818 housewives with a marriage age range of 2 to 20 yearswhich is determined based on the sampling technique in the form of purposive samplingand the slovin formula to determine the number of samples.The results of this study are the results of the regression analysis test obtained a significance valueof 0.000 <0.005 and the coefficient of determination (R square) of 0.224 and the coefficientregression x of 0.267. This shows that there is sexual influencesatisfaction of 22.4% with the level of mental health of housewives and 70.6% is influenced by other factors such as environment, economic conditions and maturitythink.